Modulation of dynamic aggregation in fluorogenic SNAP‐tag probes for long‐term super‐resolution imaging. Issue 2 (29th July 2022) - Qiao, Qinglong; Liu, Wenjuan; Chi, Weijie; Chen, Jie; Zhou, Wei; Xu, Ning; Li, Jin; Fang, Xiangning; Tao, Yi; Zhang, Yinchan; Chen, Yingzhu; Miao, Lu; et al.
Abstract: The combination of super‐resolution microscopy and synthetic fluorescence probes has emerged as a universal tool to monitor dynamic biological events at the nanometer scale. However, the limited site‐specificity and fluorogenicity of synthetic fluorescent probes make it still difficult to realize long‐term super‐resolution imaging. Herein, we introduce a dynamic aggregation mediated SNAP‐tag fluorogenic probe, BGAN‐Aze, which can specifically bind to various SNAP‐tag fusion proteins with 41‐fold fluorescence enhancement. The equilibrium between the non‐fluorescent aggregate/dimer (A–D) and the fluorescent monomer (M) of BGAN‐Aze acts as an effective method to reduce the fluorescence background and endow BGAN‐Aze with the capability of conducting washing‐free super‐resolution imaging of various intracellular and extracellular proteins. Using this probe, we monitored multiple dynamic biological events, such as MMC, mitophagy, the fusion of nucleolus, and the growth and contact of filopodia. We expect that BGAN‐Aze will become a widely used SNAP‐tag for super‐resolution imaging of dynamic biological events and the A–D–M equilibrium can be a general strategy for designing fluorogenic probes. Abstract : Through the A–D–M equilibrium of BGAN‐Aze, we developed a fluorogenic SNAP‐tag probe and realized long‐term super‐resolution imaging of universal intracellular and extracellular proteins.